Exploration of Marine Tourism in Watulimo, Trenggalek Regency: Challenges, Potentials, and Development Strategies - Rita Parmawati; Amin Setyo Leksono; Bagyo Yanuwiadi; Agung Sih Kurnianto (Journal of Indonesian Tourism and Development Studies, 2017)
Watulimo District, Trenggalek Regency is one of the area in East Java Province that has an abundant marine potential. However, this huge potential has not been optimally developed in a form of marine tourism. This study aims to determine internal and external factors that influence the development of marine tourism in Watulimo Subdistrict, Trenggalek, and develop a strategy of marine tourism development in a sustainable manner. This study was conducted on 4 beaches in Watulimo Subdistrict, Trenggalek Regency: Prigi, Karanggongso, Cengkrong, and Damas. Interviews were conducted by using semi-structured technique. Secondary data is obtained from government policy documents relating to tourism; tourism infrastructure facilities in the research location; data of tourist visits; geography and demographics; socio-cultural and economic data. Most respondents believe that promotion (0.083) and tourist information center (0.075) indicator are considered very important. Advances in information technology have the highest weight (0.097), where respondents can know about the state of the marine tourism area based on information and reviews. The results show the number of scores obtained from the weighting and external factor rating of 2.656 (good value range), which illustrates that the marine tourism area in Watulimo has an opportunity in its development. Cooperation with travel agents, hotels, restaurants, and tourist information centers for Trenggalek District can be incorporated into their brochures to increase traffic.Keywords: development, information, promotion, tourism, Watulimo.